‘Killing the Tree by Cutting the Foliage Instead of Uprooting It?’ Rethinking awareness campaigns as a response to trafficking in South-West Nigeria - Olayiwola, Peter (Anti-Trafficking Review, 2019)
Child domestic work is one of the issues often connected with human trafficking in popular discourses. The idea of ignorant and unsuspecting parents and children being tricked into situations of trafficking for domestic labour is rife and has driven education and awareness campaigns as keys to addressing trafficking. This paper offers a critique of awareness creation as an anti-trafficking strategy. Based on an ethnographic study of child domestic work in South-West Nigeria and an analysis of secondary sources, this article reviews the ignorance assumption in trafficking discourses. It contends that the existing strategy of awareness creation, often framed to discourage migration and work, misrepresents young domestic workers and/or their parents and fails to address the issues that children and/or their parents are faced with. The paper concludes by arguing for the need to address the structural root causes of trafficking rather than simply raise awareness of individual migrants.